Recurrence rate of different techniques for repair of coarctation of aorta: A 10 years experience - Dehaki Maziar; Ghavidel Alireza; Givtaj Nader; Omrani Gholamreza; Salehi Shahyad (Wolters Kluwer Medknow Publications, 2010)
Background and Aim : The main goal of this study was to assess the frequency of recurrent coarctation after repair using different surgical methods. Methods : Surgical results of repairs for coarctation of aorta (Co-A) in 188 patients under the age 14 years who were treated in Rajaee Heart Center, Tehran, Iran, were evaluated retrospectively. The most common methods included patch-graft aortoplasty (59%), resection with end-to-end anastomosis (20.7%) and subclavian flap aortoplasty (SCFA) (16.5%). The remaining patients underwent bypass tube graft and excision with placement of a tube graft. Seventy eight percent had discrete stenosis while 22% had long segment narrowing. The patients were followed for 81.6±32.8 months. Results : The overall mortality rate was 2.6%. The highest incidence rate of recoarctation was found in the patch-graft aortoplasty group (12.7%) and the lowest was found in SCFA (3.2%). The incidence of recoarctation in long-segment lesions was significantly higher than that in the discrete ones (30% vs. 4%, P<0.001). In patients <1 year, the incidence of recoarctation was lower than that in the other age groups. Conclusion : The patch-graft aortoplasty technique had the highest incidence of recoarctation and SCFA had the lowest rate. Long-segment Co-A had a higher chance of recoarctation. In contrast to some previous reports, the incidence of recoarctation was not higher in the age below 1 year.